Dancing on our turtle's back: Stories of Nishnaabeg re-creation, resurgence, and a new emergence - Simpson, Leanne (ARP Books, 2011)
Many promote Reconciliation as a "new" way for Canada to relate to Indigenous Peoples. In Dancing on Our Turtle's Back: Stories of Nishnaabeg Re-Creation, Resurgence, and a New Emergence activist, editor, and educator Leanne Simpson asserts reconciliation must be grounded in political resurgence and must support the regeneration of Indigenous languages, oral cultures, and traditions of governance. Simpson explores philosophies and pathways of regeneration, resurgence, and a new emergence through the Nishnaabeg language, Creation Stories, walks with Elders and children, celebrations and protests, and meditations on these experiences. She stresses the importance of illuminating Indigenous intellectual traditions to transform their relationship to the Canadian state. Challenging and original, Dancing on Our Turtle's Back provides a valuable new perspective on the struggles of Indigenous Peoples.
Keywords: amériques; approches et analyses; autochtones; canada; com5170; cours; cycles supérieurs; discipline; fem1000; fem3600; fem7000; féminisme autochtone; féminisme décolonial; linguistique; lit2815; lit3220; politique; premier cycle; réconciliation; régions géographiques; sciences humaines

Land as pedagogy: Nishnaabeg intelligence and rebellious transformation - Simpson, Leanne Betasamosake (Decolonization: Indigeneity, Education & Society, 2014)
A resurgence of Indigenous political cultures, governances and nation-building requires generations of Indigenous peoples to grow up intimately and strongly connected to our homelands, immersed in our languages and spiritualities, and embodying our traditions of agency, leadership, decision-making and diplomacy. This requires a radical break from state education systems – systems that are primarily designed to produce communities of individuals willing to uphold settler colonialism. This paper uses Nishnaabeg stories to advocate for a reclamation of land as pedagogy, both as process and context for Nishnaabeg intelligence, in order to nurture a generation of Indigenous peoples that have the skills, knowledge and values to rebuild our nation according to the word views and values of Nishnaabeg culture.
Number: 3
Keywords: amériques; approches et analyses; canada; cours; discipline; environnement; féminisme autochtone; histoire et politique; nishnaabeg; pol4105; premier cycle; premières nations; pédagogie; pédagogie nishnaabeg; régions géographiques; résistance; résurgence; savoirs autochtones; sciences de l'éducation; sciences humaines; sociologie; système colonial; systèmes d'oppressions; systèmes éducatifs; territoire nishnaabeg; thématiques; éducation par le territoire